Hemodynamic profile of pulmonary hypertension (PH) in ARDS - George Calcaianu (Pulmonary Circulation, 2018)
Acute respiratory distress syndrome (ARDS) is a diffuse lung injury that leads to a severe acute respiratory failure. Traditional diagnostic criteria for pulmonary hypertension (PH), in this situation, may be unreliable due to the effects of positive pressure ventilation and vasoactive agents. The aim of this study is to describe the hemodynamic characteristics of PH secondary to ARDS, in relation with respiratory parameters. We assessed the hemodynamic, respiratory function, and ventilator parameters in a cohort of 38 individuals with ARDS-associated PH defined by mean pulmonary arterial pressure (mPAP) ≥ 25 mmHg. Individual characteristics: PaO2/FiO2 = 110 ± 60 mmHg, alveolar-arterial oxygen gradient (A-aO2) = 549 ± 148.9 mmHg, positive end-expiratory pressure (PEEP) = 8.7 ± 3.5 cmH 2 O, pulmonary static compliance (Cstat) = 30 ± 12.1 L*cmH 2 O-1, mPAP = 35.4 ±6.6 mmHg, pulmonary artery wedge pressure (PAWP) = 15.6 ± 5.5 mmHg, cardiac index (CI) = 3.4 ± 1.2 L/min/m 2 , pulmonary vascular resistance (PVR) = 3.3 ± 1.6 Wood units (WU), right atrial pressure (RAP) = 13.4 ± 5.4 mmHg, diastolic pulmonary gradient (DPG) = 12.6 ± 6.5 mmHg, and trans-pulmonary gradient (TPG) = 19.7 ± 7.7 mmHg. The composite marker—DPG >7 mmHg and PVR > 3 WU—is associated with lower CI ( P  = 0.016), higher mPAP ( P  = 0.003), and lower pulmonary static compliance ( P  = 0.028). We confirmed a poor prognosis of ARDS associated with PH, with a 50% survival rate after 17 days. We observed that the survival rate at 28 days was better in the case of improvement in the PaO2/FiO2 ratio in the first 24 h (log rank P  = 0.003). ARDS associated with PH is a severe condition with a very poor survival rate. The composite marker DPG > 7 mmHg and PVR > 3 WU seemed to better describe the hemodynamic and respiratory dysfunction. The improvement in PaO2/FiO2 ratio in the first 24 h defined a better survival in our cohort of patients.